Experimental investigation on large-aspect-ratio zirconia ceramic microchannels by waterjet-assisted laser processing - Qingqing Qiu; Jinjin Han; Aqib Mashood Khan; Rui Ma; Bin He; Linglei Kong; Qilin Li; Kai Ding; Wasim Ahmad; Weining Lei (Alexandria Engineering Journal)
Zirconia (ZrO2) ceramic has excellent mechanical properties and superior chemical stability, making it widely used in aerospace, microelectronics, biomedicine, and mechanical manufacturing. However, due to its difficult-to-machine characteristics, traditional machining methods struggle with fabricating large-aspect-ratio (LAR) microchannels in zirconia ceramics. This study compares direct laser machining (DLM) and waterjet-assisted laser micromachining (WJALM) in preparing LAR zirconia microchannels, focusing on surface morphology, heat-affected zones, microhardness, chemical and phase composition. Subsequently, parameter experiments of WJALM were carried out to achieve superior machined quality LAR zirconia microchannels by assessing the geometric profile and ablation-area-ratio. Experimental results indicated that WJALM significantly surpasses DLM, achieving a 46 % decrease in areal surface roughness (Sa), WJALM reduced the heat-affected zone depth by approximately 37 % compared to DLM. The WJALM process also enhanced the ablation-area-ratio by 61 %, achieving superior machining quality under optimized conditions of 27 W laser power, 100 mm/s scanning speed, and 8 m/s waterjet velocity.